Kebijakan Turki dalam Menampung Pengungsi Korban Perang Saudara Suriah Tahun 2011 - 2013 - Kusuma Putri, Amalia Zatalini; Utomo, Tri Cahyo; Pattipeilohy, Shary Charlotte (Journal of International Relations, 2015)
Syrian conflict which been transformed into civil war led to the emergence of refugee crisis. Syrian refugees themselves have been accommodated in Turkey since the beggining of conflict in 2011. Turkish government imposed the temporary protection regime policy for Syrian refugees which was declared in October 2011. By the enactment of temporary protection regime policy, the Turkish government suspended the geographical limitation that previously were the characteristic of Turkey’s asylum policy. This undergraduate thesis aims to seek for Turkey’s national interest through its policy on accepting Syrian refugees peroid 2011-2013. This research is done in explanatif type using case study method. The result of this research shows that Turkey’s willingness on accepting Syrian refugees is motivated by Turkey’s interest to realize the regime change in Syria.